Study on the damage effect of 12.7 mm armour piercing incendiary projectile penetrating aramid reinforced concrete slab - Gao, Zhen; Wang, Zhenqing; Chen, Yeqing; Li, Shutao; Li, Lumeng; Chen, Longming; Huang, Chenglong; Yang, Qingyuan (Computers & structures, 2025)
The resilience of reinforced concrete to local damage and penetration has been a subject of interest for many decades. In recent years, aramid fibres and composite laminates have emerged as high-performance engineering materials that are widely used in protective structures. In this paper, four kinds of specimens of reinforced concrete (RC), aramid fiber reinforced concrete (AFRC), aramid fiber reinforced plastic reinforced concrete and aramid fiber reinforced plastic reinforced concrete were made, and the failure characteristics and penetration resistance of different members were analyzed and compared through the impact test of 12.7 mm armor piercing incendiary bomb. Moreover, the finite element model was established and subsequently validated by the test results. A numerical simulation was employed to analyze the structural failure modes resulting from the impact of varying projectile velocities. The underlying mechanism by which the damage is caused can be observed by monitoring the propagation of stress waves. A dimensional analysis method was employed to fit the empirical formula relating the failure characteristics of reinforced concrete slabs (residual velocity, crater diameter, crater depth) and initial velocity. The impact of three key parameters on the penetration resistance of the composite structure was investigated, including the strength grade of concrete, the thickness of the aramid layer and the varying thickness ratio of concrete/aramid at a consistent surface density. The experimental and numerical simulation results show that aramid fiber reinforced concrete structures cannot improve the penetration resistance of the slab. The penetration resistance of reinforced concrete slabs reinforced with aramid laminates on the back is better than that of ordinary concrete slabs. Furthermore, the area density of the composite target plate is optimised when the thickness ratio of the reinforced concrete/aramid layer dC/dA is equal to 2. This configuration exhibits the most efficient anti-penetration characteristics. The research results can be used as one of the basis for the optimization design of high-efficiency protective structure of composite structure.